Evaluation of the therapeutic effect against benign prostatic hyperplasia and the active constituents from Epilobium angustifolium L. (25th March 2019) - Deng, Liqing; Zong, Wei; Tao, Xueying; Liu, Shuang; Feng, Zhiying; Lin, Yuping; Liao, Zhihua; Chen, Min
Abstract: Ethnopharmacological relevance: Plants of Epilobium angustifolium are popular in China to treatment of traumatic injury, subduing inflammation and menstrual disorders. In European, the preparations or extracts containing E. angustifolium are popular to treat prostate diseases. Recent research suggested that E. angustifolium showed therapeutic effects in early stage of BPH, inflammation of urethra and prostate, as well as micturition problems. And the related researches were focus on aqueous extract and its main constituent of oenothein B. Aim of the study: This study aims to evaluate the therapeutic effect against BPH of the ethyl acetate extracts (EAE) and n -butanol extracts (BUE) from E. angustifolium and to chemical investigation of the active constituents. Materials and methods: The in vitro anti-BPH activity was assessed by determining the benign prostatic hyperplasia epithelial-1 (BPH-1) cell viability using MTT assay as well as suppressing of prostate specific antigen (PSA) secretion in prostate epithelial cancer hormone-dependent (LNCaP) cells measured by ELISA method. The in vivo anti-BPH was evaluated by testosterone propionate induced BPH SD rats. After oral administration of BUE at 100, 200 and 400 mg/kg B.W. for 28 days, the prostate weight and index, plasma androgen level, histopathological alteration, oxidative and inflammatory-related factors in prostate were assessed. Phytochemical investigation on active extracts was carried by chromatographic and spectroscopic techniques. Anti-BPH activities of the isolates were evaluated in vitro . Results: BUE and EAE from E. angustifolium exhibited significant anti-BPH effect in vitro. Further in vivo study demonstrated that BUE exhibited therapeutic effects against TP-induced BPH in SD rats via down-regulating of the androgen level, suppressing the expression of NF-κB and eventually alleviating the inflammatory responses and oxidative stress. Phytochemical research on BUE and EAE extracts led to the isolation and identification of 50 compounds. In vitro anti-BPH screening revealed that 26 compounds exhibited anti-proliferation in BHP-1 cell and 36 compounds showed PSA inhibition in LNCap cell, in which 7 compounds exhibited very significant anti-BPH activities in both two cell lines ( P < 0.01), 5 compounds with extremely significant activities in one of the cell lines ( P < 0.001), and compound25 exhibited the most potent anti-BPH activity ( P < 0.001). Conclusions: E. angustifolium exhibited the therapeutic potential against BPH, and its active compounds may be used as candidate for treatment of BPH. Graphical abstract: